2006 Ieee/Aiaa 25TH Digital Avionics Systems Conference 2006
DOI: 10.1109/dasc.2006.313670
|View full text |Cite
|
Sign up to set email alerts
|

B-VHF - Selected Simulation Results and Assessment

Abstract: B-VHF is a proposal for a future aeronautical communication system in the VHF band based on an overlay concept, i.e. during the transition phase the B-VHF system shares the same frequency band with legacy VHF systems without interfering with them. In this paper, the overlay concept is evaluated by simulations of the physical and higher layers. Simulation results show that the B-VHF overlay system works in presence of interference from legacy VHF systems. The protocol is designed to allow using the available re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The second algorithm is a data aided maximum likelihood synchronizer that exploits information about the spectrum allocation available after the net entry phase. Simulation results in [8,9] have shown that the proposed synchronization algorithms work properly in presence of NBI.…”
Section: Phylayer Designmentioning
confidence: 96%
See 1 more Smart Citation
“…The second algorithm is a data aided maximum likelihood synchronizer that exploits information about the spectrum allocation available after the net entry phase. Simulation results in [8,9] have shown that the proposed synchronization algorithms work properly in presence of NBI.…”
Section: Phylayer Designmentioning
confidence: 96%
“…10 presents our results for an En-Route 2015 scenario with high, medium, and low cell population (for a description of the simulation scenarios see [8] and the next section). The expected medium access delay increases almost exponentially as the amount of available slots decreases.…”
Section: Completion Rate and Expected Waiting Time This Markovmentioning
confidence: 98%
“…All technologies are summarized in figure 1. LDACS was developed in cooperation between the German Aerospace Center (DLR) [5], [11], Frequentis AG [12], and the University of Salzburg in Austria [13], [14] with its origins in merging parts of the B-VHF [15], B-AMC [16]- [18], TIA-902 (P34) [33], and WiMAX IEEE 802.16e technologies [19].…”
Section: Introductionmentioning
confidence: 99%
“…B-AMC stands for Broadband Aeronautical Multicarrier Communications and is based on Broadband-VHF (B-VHF) [1,2]. B-VHF 2 was a feasibility study which demonstrated the suitability of multi-carrier based wideband technologies for aeronautical communications.…”
Section: Introductionmentioning
confidence: 99%